THE IMPACT OF MACRO FACTORS ON COMPOSITE STOCK PRICE INDEX (CSPI) IN INDONESIA STOCK EXCHANGE (IDX) PERIOD 2014-2018 - Djamaluddin, Said; Riki Ardoni; Aty Herawati (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to determine the effect of the BI rate, the dollar exchange rate, the yuan exchange rate, the Dow Jones index, the Shanghai index and world oil prices on the composite stock price index (CSPI). The data used is the period from January 2014 to December 2018 with the multiple regression analysis method. The results showed that the BI rate, Dollar Exchange, Yuan Exchange, Dow Jones, SSE Composite Index and WTI were able to explain the 91.8% effect on CSPI and the remaining 8.2% explained by other variables not examined. T test results show that partially BI interest rates, the yuan and Shanghai exchange rates do not have a significant effect on CSPI. While the dollar exchange rate, Dow Jones Index and world crude oil prices have a significant influence on the composite stock price index (CSPI) with coefficients respectively - 0.41705, +0.21245 and -7.86373. The independent variable that has the most dominant influence on CSPI is Crude Oil (WTI).